INTEGRATION OF KULIYYATU-L MU’ALLIMIN AL-ISLAMIYAH (KMI) CURRICULUM AND MERDEKA CURRICULUM - Nuhzatul Ainiyah; Nunuk Hariyati; Muhammad Sholeh (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2025)
This study aims to describe the integration forms and strategies of the Kulliyatu-l Mu’allimin Al-Islamiyyah (KMI) Gontor Curriculum and the Merdeka Curriculum at SMA Islam Al-Ishlah Tajug Indramayu. Furthermore, it analyzes the roles of teachers and institutional policies, identifies supporting and inhibiting factors, and examines the impact of this integration on students’ character, academic performance, and independence. This research employs a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model. The findings reveal that curriculum integration is executed through structural and practical approaches. Structurally, the school combines both curricula within learning schedules, teaching modules, and a dual assessment system. Practically, integration is evident in trilingual instruction (Arabic, English, and Indonesian), character-based and project-based learning, and a 24-hour boarding system.